STRATEGI MUTU TERPADU: KONSEP DAN KARAKTERISTIK TOTAL QUALITY MANAGEMENT - Maudinah, Nur Hikmah; Ramli, Muhammad; Hasan, Mardhiah (Educational Leadership: Jurnal Manajemen Pendidikan, 2025)
Total Quality Management (TQM) is a managerial approach that emphasizes continuous quality improvement through the involvement of all members of an organization. In the context of Islamic educational institutions, the application of TQM is essential to address the challenges of educational quality in the global era. This study discusses the fundamental concepts of TQM, its main characteristics, and its relevance and application in Islamic educational institutions. It emphasizes that TQM is not only focused on outcomes but also on processes, active participation of all components, and stakeholder satisfaction. By applying TQM principles such as visionary leadership, continuous improvement, customer focus, and total involvement, Islamic educational institutions can enhance the overall and sustainable quality of their educational services.